2022
DOI: 10.1038/s41467-022-33683-1
|View full text |Cite
|
Sign up to set email alerts
|

Polarized NHE1 and SWELL1 regulate migration direction, efficiency and metastasis

Abstract: Cell migration regulates diverse (patho)physiological processes, including cancer metastasis. According to the Osmotic Engine Model, polarization of NHE1 at the leading edge of confined cells facilitates water uptake, cell protrusion and motility. The physiological relevance of the Osmotic Engine Model and the identity of molecules mediating cell rear shrinkage remain elusive. Here, we demonstrate that NHE1 and SWELL1 preferentially polarize at the cell leading and trailing edges, respectively, mediate cell vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 53 publications
2
22
2
Order By: Relevance
“…In this study, we observed a novel phenomenon in which migrating MDA-MB-231 cells in soft collagen microtracks can be primed in confinement to change migratory behavior. Consistent with recent findings by other groups suggesting that confinement increases polarization of migratory equipment, 12,13,29 we observe that the increased matrix contact in confined microtracks correlates with the polarization of key machinery, like actin and active mitochondria, which may allow for fast migration after priming in confinement. Furthermore, the loss of active mitochondrial localization to the front of a migrating cell when the focal adhesion protein, vinculin, is knocked out correlates with a decrease in cell speed after exit from confinement, suggesting a disruption of memory.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we observed a novel phenomenon in which migrating MDA-MB-231 cells in soft collagen microtracks can be primed in confinement to change migratory behavior. Consistent with recent findings by other groups suggesting that confinement increases polarization of migratory equipment, 12,13,29 we observe that the increased matrix contact in confined microtracks correlates with the polarization of key machinery, like actin and active mitochondria, which may allow for fast migration after priming in confinement. Furthermore, the loss of active mitochondrial localization to the front of a migrating cell when the focal adhesion protein, vinculin, is knocked out correlates with a decrease in cell speed after exit from confinement, suggesting a disruption of memory.…”
Section: Discussionsupporting
confidence: 91%
“…While typical mesenchymal migration relies on adhesion-based cycling of leading-edge protrusion and rearcontraction, in highly conned, PDMS microchannels, cells have been shown to adopt an amoeboid phenotype that utilizes fewer adhesions and bleb-based motility to squeeze through tight spaces. 1,[8][9][10][11] Several methods for conned migration have been observed, including the ion gradient-driven osmotic engine model 12,13 and the pressure-driven nuclear piston model. 14 It has recently been shown that the polarization of key plasma membrane proteins, NHE1 and SWELL1, regulates isotonic swelling of MDA-MB-231 cells to regulate and increase the efficiency on conned migration.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the role of other membrane proteins and ion transporters involved in cell migration and dissemination, Zhang et al. recently discovered that, while NHE1 is known to localize at the cell front of migrating cells, chloride channel SWELL1 preferentially polarizes at the trailing edge of MDA‐MB‐231 breast cancer cells 29 . SWELL1 orchestrates local cell volume shrinkage at the rear and facilitates, together with simultaneous NHE1‐mediated isosmotic cell swelling at the front, coordinated cell locomotion and cell evasion from tumour spheroids.…”
Section: Discussionmentioning
confidence: 99%
“…The most important is that we transfected the NHE1 overexpression plasmid to prove that NHE1 played a role in this process. Meanwhile, studies have shown that NHE1 polarization occurs during cell migration 66 . Inhibition of AKT and MEK1/2 can affect the migration of NHE1 to the cell membrane, thus affecting the activity of NHE1 and inhibiting cell migration 67 .…”
Section: Discussionmentioning
confidence: 99%